Formulasi Penambahan Pati Jagung pada Kukis Mocaf (Modified Cassava Flour) Vegan dengan Fortifikasi Tepung Kelor - Nofrida, Rini; Shafira, Nurul Aulia; Alamsyah, Ahmad (Pro Food, 2024)
This study aims to determine the effect of the addition of corn starch concentration on the characteristics of mocaf vegan cookies with Moringa flour fortification. This study used a completely randomized design (CRD) with 5 treatments in the form of the effect of adding corn starch, namely P0 (0%), P1 (15%), P2 (20%), P3 (25%), P4 (30%) which were repeated 3 times to obtain 15 experimental units. Parameters tested were moisture content, ash content, protein content, texture, organoleptic tests and then nutrient content and % Nutrition Adequacy Rate (RDA) in the best formula based on the Organoleptic tests. The analysis was carried out using analysis of variance at the 5% level using Co-Stat. There is a significant difference, a further test was carried out using the Honest Significant Difference (HSD) test. The results showed that the addition of corn starch had significantly different effects on moisture content, ash content, physical quality of texture, organoleptic texture (hedonic and scoring),  and had no significant effect on protein content on mocaf vegan cookies with moringa flour fortification. The higher the addition of corn starch causes a decrease in the water content and the resulting texture increases. The best treatment at P2 produced cookies with the best texture with a texture test result of 16.39 N; with a crunchy texture and organoleptically liked by panelists; with a water content of 2.4%, ash content of 1.75%, protein content of 2.85%.